The yin-yang of platelet granules - Abrams, Charles S. (American Society of Hematology, 2008)
In this issue of Blood, Italiano and colleagues reveal that platelets possess distinct granules containing specific angiogenesis-modifying factors that are selectively secreted following particular stimuli.